192k views
3 votes
Please find the derivative of
\displaystyle \frac{e^{(3)/(x)}}{x^2}. Show all work necessary - thanks!

User PSpeed
by
5.0k points

2 Answers

3 votes

Answer:


\displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)}}{x^4} - \frac{2e^{(3)/(x)}}{x^3}

General Formulas and Concepts:

Pre-Algebra

  • Splitting Fractions

Algebra I

  • Terms/Coefficients
  • Factoring
  • Exponential Rule [Multiplying]:
    \displaystyle b^m \cdot b^n = b^(m + n)

Calculus

Derivatives

Derivative Notation

Basic Power Rule:

  • f(x) = cxⁿ
  • f’(x) = c·nxⁿ⁻¹

Derivative Rule:
\displaystyle (d)/(dx) [e^u]=e^u \cdot u'

Quotient Rule:
\displaystyle (d)/(dx) [(f(x))/(g(x)) ]=(g(x)f'(x)-g'(x)f(x))/(g^2(x))

Explanation:

Step 1: Define


\displaystyle \frac{e^{(3)/(x)}}{x^2}\\f(x) = e^{(3)/(x)}\\g(x) = x^2

Step 2: Differentiate

  1. Quotient Rule:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{(d)/(dx)[e^{(3)/(x)}] \cdot x^2 - (d)/(dx)[x^2] \cdot e^{(3)/(x)}}{(x^2)^2}
  2. Derivative Rule:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{e^{(3)/(x)} \cdot (-3)/(x^2) \cdot x^2 - (d)/(dx)[x^2] \cdot e^{(3)/(x)}}{(x^2)^2}
  3. [Simplify] Multiply:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - (d)/(dx)[x^2] \cdot e^{(3)/(x)}}{(x^2)^2}
  4. Basic Power Rule:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2x^(2-1) \cdot e^{(3)/(x)}}{(x^2)^2}
  5. [Simplify] Subtract Exponents:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2x \cdot e^{(3)/(x)}}{(x^2)^2}
  6. [Simplify] Multiply:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2xe^{(3)/(x)}}{(x^2)^2}
  7. [Simplify] Exponent Rule:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2xe^{(3)/(x)}}{x^(2 + 2)}
  8. [Simplify] Add Exponents:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2xe^{(3)/(x)}}{x^4}
  9. [Simplify] Fraction Split:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)}}{x^4} - \frac{2xe^{(3)/(x)}}{x^4}
  10. [Simplify - 2nd Fraction] Cancel Like Terms:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)}}{x^4} - \frac{2e^{(3)/(x)}}{x^3}

And we have our final answer!

User Janne Valkealahti
by
5.2k points
6 votes

Hello! :)


\large\boxed{\frac{-e^{(3)/(x)} (3 + 2x )}{x^(4)}}

Find the derivative using the quotient rule:


(f(x))/(g(x)) = (g(x) * f'(x) - f(x) * g'(x))/((g(x))^(2))

In this instance:


f(x) = e^{(3)/(x) }\\\\g(x) = x^(2)

Use the following properties to find the derivative of f(x) and g(x):


e^(u) = u' * e^(u)\\\\x^(n) = nx^(n-1)

Use the quotient rule:


\frac{x^(2) * (e^{(3)/(x)} * (-3x^(-2))) - e^{(3)/(x)} * 2x }{(x^(2) )^(2)}

Simplify the numerator:


\frac{(e^{(3)/(x)} * (-3)) - e^{(3)/(x)} * 2x }{(x^(2) )^(2)}

Factor out
e^{(3)/(x)}


\frac{e^{(3)/(x)} (-3 - 2x )}{x^(4)}

Factor out -1 from the numerator:


\frac{-e^{(3)/(x)} (3 + 2x )}{x^(4)}

And we're done! Thanks for posting the question to my 1000th answer!

User Mohammad Zargarani
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.